Pedagogical Outdoor Project in Nature Sloyd - Sandven, Jostein (Techne serien - Forskning i slöjdpedagogik och slöjdvetenskap, 2024)
This study investigated the pedagogical value of a nature sloyd project. The assignment was to create the interior of and add decoration to one of the domed caves in a snow hotel dedicated to newlyweds. The theoretical understanding that led to solve the design assignment was derived from experience-based teaching. The students were interviewed during the process, and three months later, the interviews emphasised the students’ experiences, cooperation, and learning and understanding of significant subjects in the process. The Nordic context added value to the project. To support the interview data, the researcher’s memos and photos of the process were included in the analysis. The collected data were analysed in accordance with the constructing grounded theory method. The results show that feedback from supervisors and outsiders is important for maintaining motivation for a demanding outdoor project. They also show that the students were absorbed in the joy that various parts of the work process brought them, and it was new to them that ice can be processed with almost all types of tools found in a workshop for woodworking. Collaboration in lifting and constructing large structures using snow and ice made it possible for students to think in terms of a holistic design methodology. In such a way that the students reflected on didactic issues that may face them in their future profession as teachers. The results contribute to the understanding of the educational possibilities of pedagogical nature sloyd. Keywords: pedagogical value, sloyd, design art and crafts, nature sloyd